Retention of Young Skilled Graduates in Manufacturing Industries in South Africa - Mogorosi, K.; Emwanu, B. (The South African Journal of Industrial Engineering, 2025)
Although the manufacturing sector is crucial to the South African economy, it faces problems with attracting and retaining young professionals. This study investigated the factors affecting retention, such as satisfying and dissatisfying factors, the considerations that attract qualified youth to a career in manufacturing, and why they leave. A survey of 99 conveniently sampled young engineering graduates, technicians, artisans, and students in the engineering field was carried out. Important enablers of and difficulties with job retention were identified. The top three factors affecting retention were the availability of career growth opportunities, competitive salary and benefits, and promotion of a work–life balance. The study also found the emerging factors that young graduates seeking initial employment consider, including its alignment with their personal interests and their long-term goals, diversity and inclusion, and the company’s reputation. These may become more important in the future. Despite its limitations, the study has implications for educators, economic planners, employers in manufacturing firms, policy-makers, and engineering associations.